EFL STUDENTS’ PERCEPTIONS OF USING YOUTUBE IN AN ACADEMIC LISTENING CLASS - Tiara Pramesi Dewi (Wiralodra English Journal, 2023)
The purpose of this research is to explore EFL students’ perceptions about using YouTube in an EFL listening class to confirm the benefits of using YouTube in enhancing EFL students’ listening ability, particularly during the Covid-19 pandemic. Using descriptive qualitative research method, the data were collected through semi-structured interviews with five university students. The results of this research indicate that YouTube visuals help students to understand better, YouTube features help students to do note-taking, and YouTube helps students to improve listening skills. YouTube needs a good internet connection, YouTube has various content, and YouTube unsubtitled videos are students’ perceptions toward the use of YouTube in their online academic listening classes. This study is expected to give some practical ideas about how YouTube can be used in an EFL listening class to support EFL students in improving their listening skills. This research can give opportunities for further research to explore more about how YouTube affects students’ goals in other listening classes, what other platforms students might use in their listening classes, and how much these platforms have contributed to the students’ listening skill improvements.